2023
DOI: 10.1021/acsami.3c04214
|View full text |Cite
|
Sign up to set email alerts
|

Induced Red Circularly Polarized Luminescence Emission Promoted by Intermolecular Förster Resonance Energy Transfer through a Cholesteric Liquid Crystal Medium

Abstract: In this paper, planar chiral helicenes based on [2.2]paracyclophane PCPH5 acted as both chiral inducers and energy donors to construct the circularly polarized luminescence (CPL)-active ternary cholesteric liquid crystals (T-N*-LCs) in a commercial nematic liquid crystal (SLC1717, N-LCs) medium. Induced red CPL emission based on the energy acceptor of the achiral polymer DTBTF8 could be successfully promoted by the intermolecular Förster resonance energy transfer mechanism. The resulting T-N*-LCs can generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Circularly polarized luminescence (CPL) refers to the phenomenon in which chiral luminescent materials emit left-handed circularly polarized light and right-handed circularly polarized light with intensity differences after being excited. CPL materials have attracted considerable attention in recent years because of their potential applications in anticounterfeiting and encryption, circularly polarized laser, optoelectronic device, , chiral optical material, and so forth. Therefore, how to effectively construct CPL materials has attracted widespread attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Circularly polarized luminescence (CPL) refers to the phenomenon in which chiral luminescent materials emit left-handed circularly polarized light and right-handed circularly polarized light with intensity differences after being excited. CPL materials have attracted considerable attention in recent years because of their potential applications in anticounterfeiting and encryption, circularly polarized laser, optoelectronic device, , chiral optical material, and so forth. Therefore, how to effectively construct CPL materials has attracted widespread attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, liquid crystals have aroused interest in the generation of circularly polarised light due to their excellent selforganisation properties [34][35][36] and some groups have reported a high g lum value by doping a chiral emitter into an achiral liquid crystal, proving that the liquid crystal can amplify the g lum value. 35,37 Very recently, Li et al achieved a strong CPL signal of |g lum | = 0.47 using the orientational order parameter of achiral dyes in cholesteric liquid crystal media. 38 Our previous work also demonstrated that integrating liquid crystallinity and phosphorescence can lead to impressive values of g lum of 10 À2 in an OLED device.…”
Section: Introductionmentioning
confidence: 99%
“…5 In many functional applications, CPL-active materials are highly coveted by researchers for their versatile applications in optical information storage, 6,7 asymmetric catalysis, 8 3D display, 9 anti-counterfeiting, 10 and various other specialized fields. 11–17 At present, many mature strategies have been developed for constructing CPL-active materials through [2.2]paracyclophane frameworks, 18,19 such as directly covalent bonding with chromophores, 20,21 utilizing through-space electron transfer to construct D–A systems, 22 and constructing fused ring conjugated systems. 23–28 However, these molecules were mostly obtained by multistep synthesis and tedious purification procedures, which precluded their scalability and further applications.…”
Section: Introductionmentioning
confidence: 99%